2010
DOI: 10.1186/1471-2474-11-252
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing inpatient rehabilitation length of stay following revision hip replacements: a retrospective study

Abstract: BackgroundThe annual incidence of revision hip replacements has increased in both Canada and United States, particularly in younger adults. Patients following revision hip replacements often require longer hospital length of stay (LOS) but little is known about predictors of inpatient rehabilitation LOS in this group of patients. The purpose of this study was to evaluate the socio-demographic, pre-surgery, surgery and post-surgery related factors that might influence rehabilitation LOS of inpatients following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Lastly, our results demonstrated that early application of the motor FIM helps predict LOS, such that greater scores result in shorter LOS. This is in keeping with prior studies that show that the motor FIM is a predictive tool for THA rehabilitation LOS, and more broadly with other motor performance tasks such as the timed up‐and‐go, ability to manage stairs, and overall walking distance . As patients and therapists identify specific motor goals on rehabilitation admission, those who are closer to achieving them usually require a shorter inpatient stay.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Lastly, our results demonstrated that early application of the motor FIM helps predict LOS, such that greater scores result in shorter LOS. This is in keeping with prior studies that show that the motor FIM is a predictive tool for THA rehabilitation LOS, and more broadly with other motor performance tasks such as the timed up‐and‐go, ability to manage stairs, and overall walking distance . As patients and therapists identify specific motor goals on rehabilitation admission, those who are closer to achieving them usually require a shorter inpatient stay.…”
Section: Discussionsupporting
confidence: 84%
“…When applying the minimum pain relief thresholds described by Salaffi et al in their study of chronic musculoskeletal pain patients, to our population, the obvious challenge in its interpretation is that chronic pain patients do not represent rehabilitation patients. For one, they tend to demonstrate central sensitization and pain catastrophizing behavior, and as such, smaller changes in pain are less likely to be reported as meaningful . As well, Tubach et al have previously shown that acute, severe pain symptoms require greater changes in pain to report clinically meaningful changes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients include those with significant osteolysis and loosening with increased risks for periprosthetic fracture as well as those at high risk of dislocation. However, low pre-operative function is a significant risk factor for increased LOS and predictive of worse longer-term function (Biring et al, 2007;Davis et al, 2006;Yeung et al, 2010). There are no studies of rehabilitation before RTHR but there is some evidence that exercise can improve pain, muscle strength and function before primary THR (Gill & McBurney, 2013;Skoffer, Dalgas, & Mechlenburg, 2015;Wang et al, 2016) although the size and clinical importance of these changes is debated.…”
Section: Pre-operative Carementioning
confidence: 99%
“…Outcomes after surgery are influenced by multiple factors related to the individual, mode of THR failure, procedure and surrounding care. Evidence is accumulating about important individual and surgical factors that relate to outcomes such as sex, age, level of pre-operative function, urgent versus planned procedure, hospital procedure volume (Biring, Masri, Greidanus, Duncan, & Garbuz, 2007;Briggs, 2015;Davis et al, 2006;Lübbeke et al, 2007;Singh & Lewallen, 2009;Yeung, Davis, & Soric, 2010) but the association between rehabilitation and outcomes is poorly understood (Davis et al, 2006;Yeung et al, 2010). Revision patients may receive more rehabilitation than primary THR patients but what this comprises and its effectiveness is uncertain (Bozic et al, 2015;Yeung et al, 2010).…”
mentioning
confidence: 99%
“…The incidence of total hip arthroplasties (THA) has increased over the past 2 decades [1] and is now considered to be one of the most successful surgical procedures today. Common THA procedures employ surgical approaches either anterior or posterior to the trochanter.…”
Section: Introductionmentioning
confidence: 99%